Dipeptidyl peptidase 4 inhibitor anagliptin ameliorates hypercholesterolemia in hypercholesterolemic mice through inhibition of intestinal cholesterol transport. Issue 6 (5th June 2018) - Goto, Moritaka; Furuta, Shinji; Yamashita, Satoko; Hashimoto, Hiroyuki; Yano, Wataru; Inoue, Noriyuki; Kato, Noriaki; Kaku, Kohei
Abstract: Aims/Introduction: Recent data showed that dipeptidyl peptidase 4 (DPP‐4) inhibitors exert a lipid‐lowering effect in diabetes patients. However, the mechanism of action is not yet clearly understood. We investigated the effect of anagliptin on cholesterol metabolism and transport in the small intestine using non‐diabetic hyperlipidemic animals, to clarify the mechanisms underlying the cholesterol‐lowering action. Materials and Methods: Male apolipoprotein E (ApoE)‐deficient mice were orally administered anagliptin in the normal chow. Serum cholesterol levels and lipoprotein profiles were measured, and cholesterol transport was assessed by measuring the radioactivity in the tissues after oral loading of 14 C‐labeled cholesterol ( 14 C‐Chol). In additional experiments, effects of exendin‐4 in mice and of anagliptin in DPP‐4‐deficient rats were assessed. Effects on target gene expressions in the intestine were analyzed by quantitative polymerase chain reaction in normal mice. Results: The serum total and non‐high‐density lipoprotein cholesterol concentrations decreased after anagliptin treatment in the ApoE‐deficient mice. The cholesterol‐lowering effect was predominantly observed in the chylomicron fraction. The plasma 14 C‐Chol radioactivity was significantly decreased by 26% at 2 h after cholesterol loading, and the fecal 14 C‐Chol excretion was significantly increased by 38% at 72 h. The aforementioned effects on cholesterol transport were abrogated in rats lacking DPP‐4 activity, and exendin‐4 had no effect on the 14 C‐Chol transport in ApoE‐deficient mice. Furthermore, significant decreases of the intestinal cholesterol transport‐related microsomal triglyceride transfer protein, acyl‐coenzyme A:cholesterol acyltransferase 2, ApoA2 and ApoC2 messenger ribonucleic acid expressions were observed in the mice treated with repeated doses of anagliptin. Conclusions: These findings suggest that anagliptin might exert a cholesterol‐lowering action through DPP‐4‐dependent and glucagon‐like peptide 1‐independent suppression of intestinal cholesterol transport. Abstract : Anagliptin delayed the lipid transport from intestine to systemic circulation. This effect is DPP‐4‐dependent but GLP‐1R independent manner.